Proposal of the Korean Model of Synodality in the Light of the History of the Catholic Church in Korea - Choi, Hyeon Soon (Asian Horizons, 2025)
This paper seeks to identify and propose key tasks for the Catholic Church in Korea in realizing synodality. To this end, it first provides an overview of the Korean Church’s experience of synodality during the 16th Ordinary General Assembly of the Synod of Bishops (2021–2023). During this period, the faithful in particular experienced listening, dialogue, and a renewed sense of belonging to the Church, thereby gaining a deeper understanding of the meaning of synodality. The historical traces of a synodal Church in Korea not only serve as a foundation for realizing synodality in the present and future but also offer direction for its implementation. The history of the Catholic Church in Korea vividly demonstrates both the active role of the laity and the mutual cooperation between clergy and laypeople. Today, however, the Catholic Church in Korea faces numerous challenges, including secularization, relativism, the weakening of community bonds, rampant individualism, and growing social anxiety. In this context, drawing upon the style of synodality and the heritage of faith and life embedded in the Church’s history, this paper proposes four key tasks: Stimulating and fostering the initiative of the faithful; Expanding opportunities to experience the value of journeying together; Overcoming division and alienation among groups by emphasizing the Word and the Sacraments as common points of reference; Accompanying and strengthening solidarity in the concrete realities of members’ daily lives.